PROSODIC FEATURES OF SPEECH FORMS OF ADDRESS IN ENGLISH DISCOURSE IN COMPARISON WITH DIFFERENCE INTERNATION LANGUAGES (American Journal of Interdisciplinary Research and Development, 2022)
The results of the study showed that some prosodic indicators of regional speech have a tendency to gradually increase in the direction from North to South and vice versa.